MECHANISMS OF EQUILIBRIUM AND KINETIC OXYGEN ISOTOPE EFFECTS IN SYNTHETIC ARAGONITE AT 25 ?C - Kim S.T.; Hillaire-Marcel C.; Mucci A. (My University, 2006)
Aragonite was precipitated in the laboratory at 25 °C in isotopic equilibrium with Na-Ca-Mg-Cl-CO3 solutions at two different pH values (i.e., pH = ?8.2 and ?10.8) by the constant addition method. On the basis of the oxygen isotope composition of the aragonite precipitates, it was demonstrated that the equilibrium aragonite-water fractionation factor is independent of the pH of the parent solution and equal to:1000 ln ?(aragonite s(-) H2 O) = 29.12 ? 0.09To elucidate the mechanism(s) of aragonite precipitation, the equilibrium oxygen isotope fractionations between HCO3- as well as CO32 - and H2O at 25 °C were also determined experimentally to estimate the oxygen isotope compositions of the HCO3- and CO32 - ions in the parent solutions. The isotopic composition of BaCO3 (witherite) precipitated quantitatively from solutions of various pH values and the speciation of carbonic acid species in these solutions were combined to yield the following oxygen isotope fractionation factors:1000 ln ?(HCO3- s(-) H2 O) = 30.53 ? 0.081000 ln ?(CO32-s(-) H2 O) = 23.71 ? 0.08The oxygen isotope composition of witherite obtained from two types of fractional precipitation experiments revealed that CO32 - ions are preferentially incorporated into the growing crystal. In addition, preferential deprotonation of isotopically light HCO3- ions and the incorporation of the light CO32 - isotopologues are proposed to account for the kinetic isotope effects observed in the course of aragonite and witherite precipitations.
Keywords: ARAGONITE; EXPERIMENTAL MINERALOGY; ISOTOPIC COMPOSITION; ISOTOPIC FRACTIONATION; LABORATORY METHOD; OXYGEN ISOTOPE; PH; PHASE EQUILIBRIUM; PRECIPITATION (CHEMISTRY)